2005
DOI: 10.1074/jbc.m408251200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Phosphatidylinositol 3-Kinase/Rac1 and Cdc42 Pathways in Radial Migration of Cortical Neurons

Abstract: During cortical development, newly generated neurons migrate radially toward their final positions. Although several candidate genes essential for this radial migration have been reported, the signaling pathways regulating it are largely unclear. Here we studied the role of phosphatidylinositol (PI) 3-kinase and its downstream signaling molecules in the radial migration of cortical neurons in vivo and in vitro. The expression of constitutively active and dominant-negative PI 3-kinases markedly inhibited radial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 32 publications
6
63
2
Order By: Relevance
“…We demonstrated a role for the PDK1-Akt pathway in neocortical neurons through the specific manipulation of postmitotic cells with the use of Nex Cre/+ mice or a Neurod1 promoterdependent Cre expression plasmid. Previous work suggested that Akt might be dispensable for neuronal locomotion (20). The discrepancy between our results and that earlier work (20) may be caused by differences in the experimental time course.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We demonstrated a role for the PDK1-Akt pathway in neocortical neurons through the specific manipulation of postmitotic cells with the use of Nex Cre/+ mice or a Neurod1 promoterdependent Cre expression plasmid. Previous work suggested that Akt might be dispensable for neuronal locomotion (20). The discrepancy between our results and that earlier work (20) may be caused by differences in the experimental time course.…”
Section: Discussioncontrasting
confidence: 57%
“…The PDK1-Akt axis acts downstream of PI3K, which is activated by various extracellular stimuli, and it plays key roles in many biological processes, including microtubule stabilization, cell polarization, and cell migration (16)(17)(18). PI3K activity is required for normal radial migration in the neocortex (19,20), but the contribution of the PDK1-Akt pathway to neuronal locomotion has remained elusive (20), possibly in part because of functional redundancy among the three Akt family members and the early death of Aktand PDK1-mutant mice (21)(22)(23).…”
Section: Pdk1-akt Pathway Regulates Radial Neuronal Migration and Micmentioning
confidence: 99%
“…Hence, we could not examine the effect of these inhibitors on ET-induced inhibition of the cell migration. Recently, Konno et al (45) indicated that constitutively active and dominant-negative mutants of Rac1 and Cdc42 significantly inhibited the radial migration in the neocortical slice culture.…”
Section: Discussionmentioning
confidence: 99%
“…In Vivo Electroporation-In vivo electroporation was performed on CL57/BL6 mice at postnatal day 2 (P2) (23,24). Expression vectors encoding GFP (0.2 g/l) and dominant negative Brg1(1.0 g/l) (25) were co-injected into the hind limb and electroporated with a CUY21EDIT square wave electroporator (Nepa Gene).…”
Section: Methodsmentioning
confidence: 99%